Effect of insulin insufficiency on ultrastructure and function in skeletal muscle - Chantal Kopecky; Michael Haug; Barbara Reischl; Nandan Deshpande; Bikash Manandhar; Thomas W. King; Victoria Lee; Marc R. Wilkins; Margaret Morris; Patsie Polly; Oliver Friedrich; Kerry‐Anne Rye; et al. (Wiley, 2024)
Abstract Background Decreased insulin availability and high blood glucose levels, the hallmark features of poorly controlled diabetes, drive disease progression and are associated with decreased skeletal muscle mass. We have shown that mice with β‐cell dysfunction and normal insulin sensitivity have decreased skeletal muscle mass. This project asks how insulin deficiency impacts on the structure and function of the remaining skeletal muscle in these animals. Methods Skeletal muscle function was determined by measuring exercise capacity and specific muscle strength prior to and after insulin supplementation for 28 days in 12‐week‐old mice with conditional β‐cell deletion of the ATP binding cassette transporters ABCA1 and ABCG1 (β‐DKO mice). Abca1 and Abcg1 floxed (fl/fl) mice were used as controls. RNAseq was used to quantify changes in transcripts in soleus and extensor digitorum longus muscles. Skeletal muscle and mitochondrial morphology were assessed by transmission electron microscopy. Myofibrillar Ca2+ sensitivity and maximum isometric single muscle fibre force were assessed using MyoRobot biomechatronics technology. Results RNA transcripts were significantly altered in β‐DKO mice compared with fl/fl controls (32 in extensor digitorum longus and 412 in soleus). Exercise capacity and muscle strength were significantly decreased in β‐DKO mice compared with fl/fl controls (P = 0.012), and a loss of structural integrity was also observed in skeletal muscle from the β‐DKO mice. Supplementation of β‐DKO mice with insulin restored muscle integrity, strength and expression of 13 and 16 of the dysregulated transcripts in and extensor digitorum longus and soleus muscles, respectively. Conclusions Insulin insufficiency due to β‐cell dysfunction perturbs the structure and function of skeletal muscle. These adverse effects are rectified by insulin supplementation.